n = p.q => các ước của n và khác n là 1 ; p; q
n là số hoàn chỉnh nên n = 1+ q + p
=> 1+ p + q = p.q => pq - p -q = 1 => p.(q -1) - (q-1) = 2 => (p -1). (q-1) = 2
=> p - 1 là ước của 2 => p -1 = 1 hoặc p - 1 = 2
+) p - 1 = 1 => q - 1 =2 => p = 2 và q = 3 là số ngt => n = 2.3 = 6
+) p - 1 = 2 => q - 1= 1 => q= 2 và p = 3 => n = 2.3 = 6
Vậy n = 6
n = p.q => các ước của n và khác n là 1 ; p; q
n là số hoàn chỉnh nên n = 1+ q + p
=> 1+ p + q = p.q => pq - p -q = 1 => p.(q -1) - (q-1) = 2 => (p -1). (q-1) = 2
=> p - 1 là ước của 2 => p -1 = 1 hoặc p - 1 = 2
+) p - 1 = 1 => q - 1 =2 => p = 2 và q = 3 là số ngt => n = 2.3 = 6
+) p - 1 = 2 => q - 1= 1 => q= 2 và p = 3 => n = 2.3 = 6
Vậy n = 6